Exploration of the Protective Mechanism of Naringin in the Acetaminophen-Induced Hepatic Injury by Metabolomics. (16th September 2022) - Lin, Zihan; Wang, Guanzhen; Gu, Wei; Zhao, Shengchao; Shen, Ziyi; Liu, Wei; Zheng, Guodong; Chen, Baizhong; Cai, Yi; Li, Mingxi; Wan, Chunpeng (Craig); Yan, Tingdong
Abstract : Naringin is a dihydroflavone which was found in citrus fruits. Previous studies have indicated the antiapoptotic, antioxidative stress, and anti-inflammatory effects of naringin. It can improve many common diseases, including fibrosis or hepatotoxicity, cardiovascular disease, and diabetes. Acetaminophen (APAP) is a frequently used painkiller, and hepatotoxic side effects limit its use. The purpose of the current examination is to find the impact of naringin on APAP-induced hepatic injury. Firstly, we pretreated mice model groups with naringin. Then, the liver injury model was established by injecting intraperitoneally into mice with APAP. After the mice were euthanized, we obtained serum and liver tissue samples from the mice. Finally, these samples were analyzed using a metabolomics approach to find the underlying mechanism of the effects of naringin on APAP-induced liver injury and provide a new treatment strategy for APAP-induced liver injury. Our data indicate that naringin significantly improves APAP-induced liver injury in mice and reduces the expression levels of liver injury markers in a dose-dependent manner. Furthermore, analysis of differential metabolites in mice with liver injury showed that naringin reduced APAP-induced hepatotoxicity due to reversing multiple metabolite expression levels and the rescue of energy, amino acid, and purine metabolism.